Fused filament fabrication, debinding and sintering as a low cost additive manufacturing method of 316L stainless steel - Thompson, Yvonne; Gonzalez-Gutierrez, Joamin; Kukla, Christian; Felfer, Peter (Additive Manufacturing, 2019)
By using filaments comprising metal or ceramic powders and polymer binders, solid metal and ceramic parts can be created by combining low-cost fused filament fabrication (FFF) with debinding and sintering. In this work, we explored a fabrication route using a FFF filament filled with 316 L steel powder at 55 vol.-%. We investigated the printing, debinding and sintering parameters and optimized them with respect to the mechanical properties of the final part. Special focus was placed on debinding and sintering in order to obtain components of low residual porosity. Solvent debinding of the printed green bodies created an internal network of interconnected pores and was followed by thermal debinding. Thermal debinding allowed for complete removal of the remaining binder and produced mechanically stable brown parts. Sintering at 1360 °C provided densification of the parts and generated nearly isotropic linear shrinkage of about 20%. Using optimized parameters, it was possible to fabricate 316 L steel components with a density greater than 95% via the material extrusion additive manufacturing, debinding and sintering route, with achievable deflections in a 3-point bending test similar to rolled sheet material, albeit at lower strength.
CRIS-Team Scopus Importer:2019-10-01
Keywords: Additive manufacturing; Highly filled filaments; Material extrusion; Powder metals; Sintering